Effect of intellectual, emotional and spiritual intelligence toward productivity of employee - Sunda Ariana, Priyono,; Chandra, Teddy; Cadalora Putra, Lucky (Opción, 2019)
The purpose of research is to test the influence of intellectual intelligence, spiritual intelligence and spiritual intelligence on work productivity and to test the relationship between intellectual, emotional and spiritual intelligence. As a method, we attempt to model the relationship between explanatory variables and a response variable by multiple linear regression analysis. Based on data analysis, there is simultaneous influence between intellectual, emotional and spiritual intelligence on work productivity. As a conclusion, to improve employee productivity, it is expected to increase employees’ IQ by training, which aims to increase employees’ intellectual intelligence.